Freud for All: Psychoanalysis and Mass Culture in Chile, 1920-1950 [“Freud Para Todos”: Psicoanálisis y Cultura de Masas en Chile, 1920-1950] - Ruperthuz-Honorato, L (Fundacao Oswaldo Cruz, 2017)
This article deals with the circulation and early spread of Freudianism in mass culture in Chilean society at the turn of the twentieth century. It documents the first references to Sigmund Freud in the Chilean media, the announcement of Freudian-style self-help classes, the appearance of psychoanalysts as characters in some fantasy novels, and the open lectures on psychoanalysis given by the first juvenile court judge in Santiago, the lawyer Samuel Gajardo Contreras. It explores the expectations projected onto Freudianism by the Chilean elite, and how Freud’s theories contributed to a rethinking of childhood, the family and emotional life in Chile from 1920-1950. © 2017, Fundacao Oswaldo Cruz. All rights reserved.